Comparative study of the ion-slicing mechanism of Y-cut LiNbO3 - Kai Huang; Zhongxu Li; Youquan Yan; Xiaomeng Zhao; Wenqin Li; Tiangui You; Shibin Zhang; Hongyan Zhou; Jiajie Lin; Wenhui Xu; Ailun Yi; Hao Huang; et al. (AIP Advances, 2019)
Ion-cutting of piezoelectric LiNbO3 (LN) thin film provides a material platform for the design and fabrication of novel integrated photonics and RF MEMS devices. In this paper, the ion-slicing mechanisms of He-implanted LN with different orientations are investigated. The anisotropy of film exfoliation is observed on LN wafers with different orientations. The Z-cut LN shows regular surface blistering and “plate-like” exfoliation, while the Y-cut LN shows the unique “rolled-up” exfoliation. Two types of defect, i.e. the pressure-related plateau defect and the stress-related crack defect, are observed to contribute to the film exfoliation. Moreover, the defect evolution in H-implanted LN is investigated. In comparison with the He-implanted LN, implanted H ions are mainly trapped by O-H bond and the implantation-induced strain is not strong enough, which are inadequate to form the continuous crack. Therefore the H ions are not favorable for the mass production of LNOI substrates.